Infrastructure finance in Africa through the Public Private Partnership (PPP): Is the Lekki-Epe Toll Road (Nigeria) economically sustainable? - Temitope, Ojo (Research of GSB, 2018)
The aims of the study could be highlighted as follows: 1. To review the existing academic literature on infrastructure finance, particularly in the area of road construction and the economic models adopted in the financing process. 2. To determine whether the accruing benefits from the concession of Lekki-Epe Expressway out-weighed the cost of constructing the purported road. 3. To determine whether the inflows from toll Lekki-Epe expressway can economically sustain the cost over-run on the Lekki-Epe express road concession.